If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 6) = 2x + 6 Reorder the terms: 2(6 + x) = 2x + 6 (6 * 2 + x * 2) = 2x + 6 (12 + 2x) = 2x + 6 Reorder the terms: 12 + 2x = 6 + 2x Add '-2x' to each side of the equation. 12 + 2x + -2x = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 12 + 0 = 6 + 2x + -2x 12 = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 12 = 6 + 0 12 = 6 Solving 12 = 6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 5=3r | | 19-2y-(6-4)(7y-2)+3y+15=0 | | X^2-5x-14*x-5=0 | | 21=8y-4 | | .4=16 | | c=2.2t^2-66t+655 | | .4=15 | | 2.1+10y=-7.9 | | 2(x-1)+6x=14 | | M^2=-m+20 | | x^2+y^2-10y-39=0 | | 6y+4x=-32 | | 4x+10=6x+14 | | (x-2)2+8=12 | | Y^2=15y-50 | | 3m+2+m+6+7m-16+3m=360 | | 4(4x+3)=60 | | 10-3x=4-2x | | Y^2=-9y-8 | | 4x^4-73X^3+28x^2+24x-45=0 | | 9x-2=-2(2x+4)-3(2x-2) | | a^2+11a-22=0 | | -16+5x=7(-6+8x)+3 | | 0=-16t^2+40t+2 | | (3i)(-2+6i)= | | 1x+.56=-.67 | | 5(x+3)+5=10 | | 52y=78 | | 4a+3=16 | | -0.7(0.3x-0.3)=-4.48 | | -72=-8y+12+4y-16 | | 3X+11+8=-6X+11+62 |